ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA (INCOME SMOOTHING) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sagala, Lamria (UNIKA Santo Thomas, 2014)
This study aims to determine the effect of variable profitability (ROA), financial risks (DER), firm size (LnTA) and public ownership of the income smoothing practices in manufacturing companies listed in Indonesia Stock Exchange either simultaneously or partially. The population of this research is manufacturing companies listed in Indonesia Stock Exchange in 2010-2012, as many as 135 companies. The sample was selected using purposive sampling method. The number of samples in this study were as many as 75 companies. Data collection was done by taking the documentation of financial statements of Indonesian Capital Market Directory and download the official website Indonesia Stock Exchange in www.idx.co.id and http://finance.yahoo.com. The analysis technique used is logistic regression analysis. The conclusion from this study is that the profitability (ROA), financial risks (DER), firm size (LnTA) and public ownership effect on the income smoothing. In partial, only the size of companies that have a significant effect on the income smoothing while the variable l profitability (ROA), financial risks (DER), and public ownership has no effect on the income smoothing.